Edith Stein and the Imago Trinitatis - Williams, Rowan (Teresianum, 2025)
Edith Stein’s engagement with Thomist metaphysics and phenomenology led her to develop a unique Christian philosophy that integrates theological insights with philosophical reasoning. Her work, particularly in Finite and Eternal Being, explores the interplay between essence and existence, aligning with but also diverging from the thought of her mentor, Erich Przywara. Stein’s ontology centers on the tension between form and fullness, influencing her understanding of the imago Trinitatis. She proposes that the triadic structure of divine life - being, meaning, and self-giving - is mirrored analogically in all creation. Her innovative approach offers a fresh perspective on Trinitarian thought, emphasizing relationality and participation in divine being.